The Moderating Effect of Work Engagement on Organizational Citizenship Behavior through Psychological Capital: Empirical Evidence from the Higher Education Sector - Ivan Batara; Iskandar Ali Alam; Andala Rama Putra Barusman; Defrizal Defrizal; Helmita Helmita (Business and Applied Management Journal, 2026)
This study develops and empirically tests a conceptual framework explaining how work engagement influences Organizational Citizenship Behavior (OCB) in higher education institutions, with Psychological Capital (PsyCap) as a moderating variable. The study is important because higher education institutions increasingly depend on faculty members who are willing to demonstrate discretionary behaviors beyond formal job requirements to enhance institutional effectiveness, adaptability, and long-term competitiveness. Drawing on the Resource-Based View (RBV) and Social Exchange Theory (SET), PsyCap comprising hope, efficacy, resilience, and optimism is positioned as a strategic internal resource that strengthens the translation of engagement into sustained discretionary behaviors. Using SmartPLS 4, data from 262 faculty members across private universities in Lahat, Palembang, and Pagar Alam were analyzed. Results show that work engagement significantly predicts OCB (t = 2.494, p = 0.013), while PsyCap alone does not exert a direct effect (t = 0.473, p = 0.636). However, the interaction term PsyCap × Work Engagement demonstrates a strong moderating effect (t = 5.82, p = 0.000), with R² = 0.913 and f² = 0.319, confirming excellent predictive accuracy. These findings highlight PsyCap as strategic capital that amplifies engagement into citizenship behaviors, offering theoretical enrichment and practical implications for institutional resilience and competitiveness.